Redox-Modulating and Micronutrient-Based Priming Strategies Enhance Germination and Vigour by Improving the Physiological Integrity of Onion Seeds - LAVANYA VIJ; NAVJYOT KAUR; RAJINDER SINGH (Seed Research, 2025)
Seed priming is a promising technique gaining rapid traction in agriculture for improving seed performance and ultimately crop yields, especially in high value crops such as onion, which often suffer from poor germination, vigour and emergence stand. The current study was designed to evaluate the impact of various redox-modulating salts – ascorbic acid and H2O2 and micro-nutrient based salts – Mg(NO3)2, ZnSO4, CuSO4 and FeCl3 on the germination and physiological responses of onion seeds. Laboratory and field studies were carried out in the year 2021 in a completely randomized design in Seed Physiology Laboratory, Punjab Agricultural University, Ludhiana, Punjab, India. In-vitro germination studies documented improved early seedling growth and vigour in the onion seeds primed with 0.5% and 1% ascorbic acid; 0.25% and 0.5% Mg (NO3)2 and 1% ZnSO4. These improvements could be attributed the reduced electrolyte leakage and electrical conductivity recorded which consequently translated in improved physiological integrity and seed quality in the primed seeds. Differential results were recorded in the field investigations with many lab-tested invigorating priming treatments not performing equivalently. Amongst all, onion seeds primed with 0.5% Mg (NO3)2 for 9 hours emerged as best performing priming treatment documenting a significant six percent increment (50.67%) in germination as compared to untreated onion seeds (44.67%). Higher concentrations of H2O2, CuSO4, ZnSO4 and FeCl3 were found to be detrimental, reflecting their potential to undermine seed germination and vigour through oxidative stress, greater electrolyte leakage, reduced membrane stability and poor seedling performance, thus emphasizing the necessity for careful optimization of species-and environment-specific priming concentration and duration.